Room-temperature synthesis with inert bubble templates to produce "clean" PdCoP alloy nanoparticle networks for enhanced hydrazine electro-oxidation1. Issue 13 (14th February 2015) - Ma, Yuanyuan; Wang, Rongfang; Wang, Hui; Key, Julian; Ji, Shan
<x xml:space="preserve">Abstract</x> PdCoP alloy nanoparticle networks prepared using inert bubbles as template exhibited high activity for hydrazine oxidation.